PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ISLAMIYAH PONTIANAK TENGGARA - Lilis Rustari; Fadillah Fadillah; Muhamad Ali (Universitas Tanjungpura, 2019)
AbstractThe aims of this research was to describe the emotional social development of childen aged 5-6 years at Islamiyah kindergarten Southeastern Pontianak. The method used is a descriptive method with a qualitative approach. Data subjects in this research are teacher’s and 16 childern, which consists of 7 girls and 9 boys of group B1 with aged 5-6 years Islamiyah Kindergarten Southeastern Pontianak. The techniques used in this research were observation, interview, and documentation using data collection tools like is observation guidelines, interview guides, and documentation picture. The results of data analysis show that the emotinal social development in children aged 5-6 years in the development of cooperative attitudes with friends still needs guidance and direction from the teacher. The development of tolerance with friends becomes better because of the successful direction of the teacher. Expressing self-emotion is uncommon and when it is quickly resolved the teacher. Get to know manners and manners always done by children. This habit is a mandatory material for teachers to convey to children in each learning process. Developing empathy with friends is more dominant initiated by the teacher, in the learning process children want to listen to other children and have agreed upon together. Suggestions that can be delivered are that teachers should always explain the positive and negative sides of cooperative and tolerant attitudes, explain the importance of implementing manners and manners, the benefits and disadvantages of self-emotion if it continues to develop and the importance of having a sense of empathy.Keyword : Emotional Social, Cooperative Attitudes, Child Aged 5-6 YearsAbstractThe aims of this research was to describe the emotional social development of childen aged 5-6 years at Islamiyah kindergarten Southeastern Pontianak. The method used is a descriptive method with a qualitative approach. Data subjects in this research are teacher’s and 16 childern, which consists of 7 girls and 9 boys of group B1 with aged 5-6 years Islamiyah Kindergarten Southeastern Pontianak. The techniques used in this research were observation, interview, and documentation using data collection tools like is observation guidelines, interview guides, and documentation picture. The results of data analysis show that the emotinal social development in children aged 5-6 years in the development of cooperative attitudes with friends still needs guidance and direction from the teacher. The development of tolerance with friends becomes better because of the successful direction of the teacher. Expressing self-emotion is uncommon and when it is quickly resolved the teacher. Get to know manners and manners always done by children. This habit is a mandatory material for teachers to convey to children in each learning process. Developing empathy with friends is more dominant initiated by the teacher, in the learning process children want to listen to other children and have agreed upon together. Suggestions that can be delivered are that teachers should always explain the positive and negative sides of cooperative and tolerant attitudes, explain the importance of implementing manners and manners, the benefits and disadvantages of self-emotion if it continues to develop and the importance of having a sense of empathy.Keyword : Emotional Social, Cooperative Attitudes, Child Aged 5-6 Years